Precursor preparation of Zn–Al layered double hydroxide by ball milling for enhancing adsorption and photocatalytic decoloration of methyl orange. Issue 50 (21st June 2017) - Qu, Jun; He, Xiaoman; Li, Xuewei; Ai, Ziqiang; Li, Yujie; Zhang, Qiwu; Liu, Xinzhong
Abstract : The higher photocatalytic decoloration efficiency of the precursor than that of LDH because of the synergistic effect of intercalation and catalysis. Abstract : An amorphous photocatalyst was prepared via simple dry milling of Zn basic carbonate (Zn4 CO3 (OH)6 ·H2 O) and Al hydroxide (Al(OH)3 ) as a precursor of Zn–Al layered double hydroxide (LDH) and the precursor was agitated in water to simply synthesize the Zn–Al LDH for comparison. The adsorption and photocatalytic activity of the Zn–Al LDH and the precursor were studied via the removal of methyl orange (MO) and decoloration of MO under ultraviolet light irradiation in aqueous solution, respectively. The precursor exhibits much higher decoloration efficiency towards MO than the Zn–Al LDH product because of the synergistic effect of the intercalation reaction and its photocatalytic activity. The amorphous precursor could easily incorporate MO molecules to form MO intercalated LDH, allowing easy access of the organic pollutant to the photocatalyst sample, resulting in an obvious improvement in photocatalytic performance. The novel idea to use the precursor sample instead of the synthesized final product may be applied in other fields to increase the required performances.